ACTIVITY OF ENDOFIT MOLD METABOLITES INSULATED FROM BETEL LEAVES (Piper betle L.) On FUNGUS Candida albicans - Sumiatun; Aini; Edy Kurniawan; Jumary ustiawaty (Politeknik Medica Farma Husada Mataram, 2020)
Betel (Piper betle) is a type of vines that have been long known and are used hereditary for the treatment. Fungal endophyte betel leaf producing antimicrobial substances and secondary metabolites that are used as the discovery, and production of new drugs. Candidiasis is a disease caused by Candida albicans when immune dysfunction occurs and causes diseases of the oral mucosa, the digestive tract and vagina. The use antifungal drugs from chemicals to cause side effects on candidates that many alternative treatments using natural ingredients as an antimicrobial. This research aims to isolate fungal endophyte of betel leaf (Piper betle L.) and know the activity of metabolites against the fungus Candida albicans. This research was conducted in the laboratory of Plant Physiology and Biotechnology, Faculty of agriculture, University of Mataram in May to June 2019. The research method used is Descriptive Observation. Research done by the fungal endophyte isolate of betel leaf and identify it. Samples of the betel leaves are obtained from the village of Bonjeruk, Kec. Jonggat, Kab. Central Lombok. Production of secondary metabolites of fungal endophyte was obtained with the method of fermentation and tested its activity against Candida albicans with the well diffusion method. The test germ used is obtained from the Litbangkes Laboratory of the NTB Province Hospital. The research results showed that fungal endophyte isolated from the leaves of the betel (Piper betle L.) and obtained the results of the identification of the fungal genus Cephalosporium sp and showed an inhibition zone of 30.9 mm.